EXPLORATION OF SPATIAL ARRANGEMENT CHANGES AS A FORM OF SPATIAL SUSTAINABILITY IN DWELLING. Case Study : Kilungan House in Kudus Old City, Indonesia - Anisa Anisa; Ashadi Ashadi; Finta Lissimia; Rustama Fasda Bimatukmaru (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
Space is an architectural form that is used to accommodate activities with certain functions. In a space contained activities carried out by humans and functions that represent these activities. Sometimes during this period the space undergoes changes in activity and function. Space can undergo physical and non-physical changes to respond to changes in these activities and functions. Kilungan is a local term used to refer to the tall massive fence in the Old City of Kudus. The massive fence, known as the kilungan, was built with one of the goals to provide a sense of security. Inside the kilungan house, there are at least 2 main building masses, namely the main house and the supporting buildings. The spaces in the kilungan house which have been inhabited for more than 100 years have also undergone changes in response to the spatial sustainability of the dwelling. The purpose of this study is to explore, describe, and get the meaning of changes in space in the kilungan house. This study uses an inductive qualitative method. The initial stage is to make observations to get the distribution of the kilungan house. The research area is limited to the Old City of Kudus, Indonesia. The core stage of the research is data collection and analysis carried out simultaneously inductively. Exploration is carried out on cases to obtain findings in accordance with research objectives. The results of this study were found changes in spatial arrangement in the kilungan house in the form of: (1) changes in function without changing the physical form of space, found in spaces that accommodate different activities but have the same activity pattern; (2) changing the function of changing the spatial arrangement without changing the mass of the building; (3) changes in spatial arrangement change the physical building; (4) shifting activity changes zoning (5) Determining the direction of change does not change the orientation of the building in the circle. ; (6) Spatial sustainability in residential areas is indicated by changes in activities, functions, spatial arrangement but does not change the core things which are the concept of the kilungan house. Spatial sustainability can be found in the adaptations made by building users to new functions in the spaces in the dwelling.